STUDY FENOMENOLOGI DISFUNGSI SEKSUAL PADA PRIA DIABETES MELLITUS - Hasbullah, Hasbullah; Alamsyah, Alamsyah; Samsir, Samsir (Journal of Islamic Nursing, 2019)
Abstract Diabetes mellitus as a metabolic disease plays a very important role in a person's sexual identity and physical capacity to carry out sexual activities, this is because the whole system will change and affect one's sexual health and this requires comprehensive treatment. This study aims to: explore in depth information on Sexual Dysfunction in Men with Diabetes Mellitus in Makassar Grestelina Hospital. The type of research used is qualitative with a phenomenological case study approach of observation methods, in-depth interviews, and documentation. The results of the study of the objectives of informants whose desire is libido there are 5 informants who experience less arousal, mood, ejaculation disorders that experience premature ejaculation there are 5 informants and not ejaculate 2 informants while erectile dysfunction that experiences erection is not maximal 2 informants, fast lacking 4 informants difficult for informant erections. This means that sexual dysfunction occurs in early diabetes mellitus patients as assessed from interviews with research informants. Conclusions when increasing blood sugar levels or insulin resistance can inhibit the flow of blood vessels of the gout so that it can affect sexual problems and sexual dysfunction. It is recommended that all sufferers of diabetes mellitus be expected to conduct a comprehensive health check, control blood sugar at a time and pay attention to a healthy lifestyle, regulate diet and exercise. Keywords: Sexual dysfunction, Diabetes Mellitus